Tropical vertical greenery systems: Irrigation systems, biophysical characteristics, and influential criteria - Wang, C.; Wood, Lincoln; Teo, L. (College Publishing, 2016)
Recent studies on vertical greenery systems (VGS) mainly focus on thermal performance, acoustics effects, energy savings and environmental sustainability. There are very few studies on tropical VGS irrigation systems, plants’ characteristics, and favorable installation locations, indicating that architectural professionals may lack sufficient guidance to support their design work. Through two descriptive case studies and a questionnaire survey of VGS-related professionals including gardeners, mechanical and electrical engineers, consultants, contractors, and developers, this research developed a knowledgebase for tropical vertical greenery systems irrigation systems and determined the suitability of different types of vertical greenery systems according to the biophysical characteristics of plants. The suitability for various plant characteristics has been identified to help potential users while considering vertical greenery systems irrigation systems. Suitable locations, orientations and microclimatic conditions for vertical greenery systems irrigation systems to prevent system failure have been determined. Further research focused on establishing the technical requirements for irrigation scheduling is recommended to improve the application efficiency.